2020
DOI: 10.1186/s12904-020-00633-x
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care delivery in residential aged care: bereaved family member experiences of the Supportive Hospice Aged Residential Exchange (SHARE) intervention

Abstract: Background: The supportive hospice aged residential exchange (SHARE) is a new model of palliative care education that has been designed for residential aged care. The goal of SHARE is to help clinical staff improve palliative care within residential aged care facilities and to improve specialist palliative care nurses' knowledge and skill to care for frail older people. Method: The experiences of 18 bereaved families concerning the palliative care journey (both at the start and finish of a one-year implementat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…This suggests that NHs must create an open environment in which staff, residents and FCs feel safe and comfortable sharing their feeling and thoughts. Indeed, FCs have reported that they experienced higher‐quality communication and felt more involved in care planning when a team‐based approach to end‐of‐life communication was employed (Frey et al, 2020). NH staff experienced end‐of‐life communication as a socio‐cultural space, in which both staff and FCs felt some resistance to frank communication about death.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that NHs must create an open environment in which staff, residents and FCs feel safe and comfortable sharing their feeling and thoughts. Indeed, FCs have reported that they experienced higher‐quality communication and felt more involved in care planning when a team‐based approach to end‐of‐life communication was employed (Frey et al, 2020). NH staff experienced end‐of‐life communication as a socio‐cultural space, in which both staff and FCs felt some resistance to frank communication about death.…”
Section: Discussionmentioning
confidence: 99%
“…When a team-based approach is employed, family caregivers report higher quality communication and feel more involved in care planning that allows for a better-perceived death for their relative. 76 Therefore, it is the role of all healthcare professionals to create an environment of openness so that patients and their family caregivers feel comfortable to voice their concerns regarding end-of-life issues and can be involved in planning end-of-life care.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous models have been proposed and trialled to promote optimal palliative and end of life care in care homes, and have been helpful in improving knowledge, skills and some aspects of care such as documentation of advance care plans, improved communication and support for families [15][16][17] and reduced deterioration in quality of life. 18 While these models are multifaceted they do not provide a detailed and structured assessment and response protocol to guide day-to-day palliative and end of life care nor the systems to facilitate data driven decision-making and organisational improvements.…”
Section: Pcoc Wicking Model For Residential Aged Carementioning
confidence: 99%